Pengaruh Pembelajaran Berbasis Kearifan Lokal dan Proyek Penguatan Profil Pelajar Pancasila Terhadap Pembentukan Karakter Wirausaha Siswa di SMPN 01 Pasrujambe - Likasari, Gati Ayu (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
Entrepreneurial character in SMPN 01 Pasrujambe is still low, seen from the lack of interest of students in entrepreneurship. The influence of modern lifestyle and Western culture causes problems in the family. This study examines the influence of local wisdom-based learning and the Pancasila student profile strengthening project on students' entrepreneurial character. The research method is quantitative involving 149 students, where 60 students were taken as samples. Data were collected through valid questionnaires. Analysis using linear regression and other tests showed that the learning had a positive effect on students' entrepreneurial character. This can help students be more independent and recognize local economic opportunities. It is recommended for schools to support students' learning interests and for further researchers to consider other variables.